2020
DOI: 10.11609/jott.5839.12.11.16424-16433
|View full text |Cite
|
Sign up to set email alerts
|

Habitat preference and current distribution of Chinese Pangolin (Manis pentadactyla L. 1758) in Dorokha Dungkhag, Samtse, southern Bhutan

Abstract: The Chinese Pangolin (CP), Manis pentadactyla L. is one of the two pangolin species recorded in Bhutan.  Not many studies, however, were carried out on the species in Bhutan.  The present study was carried out to assess the habitat preference and current distribution of CP, Manis pentadactyla in Dorokha Dungkhag, Samtse from January to March 2017.  Belt transect method consisting of 100 x 100 m each was used to assess the habitat preference and estimate burrow density, coupled with an extensive search of indir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 13 publications
6
12
0
Order By: Relevance
“…The gradual decreases in the number of burrows were observed with the increase in distance to water source showing significant relation between burrow distribution and distance to a water source, which is similar to the findings of Dorji et al (2020).…”
Section: Discussionsupporting
confidence: 85%
“…The gradual decreases in the number of burrows were observed with the increase in distance to water source showing significant relation between burrow distribution and distance to a water source, which is similar to the findings of Dorji et al (2020).…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies conducted in the Nagarjun forest revealed that Chinese pangolins prefer south-facing slopes (Acharya, 2001;Gurung, 1996). A study conducted by Dorji et al (2020) in Bhutan revealed that the Chinese pangolin strongly prefers NE-facing slopes followed by NW-facing slopes. Furthermore, a study conducted by Bhandari and Chalise (2014) in the Nagarjun forest of Shivapuri Nagarjun National Park also found that pangolins prefer NW-facing slopes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, local people and experts were interviewed about the ecology and behavior of Chinese pangolins, along with the date, year, and time of any encounters, and photographic evidences of rescued individuals. Additionally, an intensive literature search revealed 18 key parameters (elevation, aspect, slope, canopy cover, ground cover, presence or absence of ant and termite colonies, habitat type, soil type, forest fire frequency, livestock grazing intensity, deforestation rate, litter depth, temperature, rainfall, humidity, and the distances to the nearest water source, road, and settlement) influencing the habitat use of the Chinese pangolin across its distribution range (Bhandari & Chalise, 2014;DNPWC, 2018;Dorji et al, 2020;Katuwal et al, 2017;Suwal et al, 2020;Wu et al, 2004Wu et al, , 2020. Most of the studies that were conducted in areas similar to our geographical region and setup reported 11 habitat parameters (elevation, aspect, slope, canopy cover, ground cover, presence or absence of ant and termite colonies, habitat type, soil type, and the distances to the nearest water source, road, and settlement) to have a major influence on pangolin distribution and habitat use (Acharya et al, 2021;Aryal & Poudel, 2018;Katuwal et al, 2017;Shrestha et al, 2021;Suwal et al, 2020).…”
Section: Preliminary Surveymentioning
confidence: 99%
“…Chinese pangolins tend to inhabit broad-leaved forests because of the greater abundance of termites [ 12 ]. However, their occurrence can also be influenced by elevation, slope gradient, canopy cover, and the distance to water and human activity [ 9 , 13 , 14 , 15 ]. Chinese pangolins are nocturnal and have adapted for digging burrows which are used for hunting prey, shelter, and avoiding predators [ 12 , 16 ].…”
Section: Introductionmentioning
confidence: 99%